Ontology of the temporary artwork : Walter Benjamin, jazz and EDM - (:unkn) unknown (My University, 2019)
Coming to grips with the 1936 Walter Benjamin-Theodor Adorno controversy on the aura of the work of art and mechanical reproduction, this paper deals with the heuristic potency of the aesthetic categories Benjamin developed in order to grasp the modernity of jazz and other musical genres of the African-American musical continuum. The translation into the musical field of concepts originally created to address visual arts demonstrates that Benjamin's  nascent mediation theory is a fertile way to consider the historical becoming of jazz and its ontological originality within XXth century art. To fully do so, one must however also take into consideration the ethnomusicological knowledge accumulated on African-American music since this debate. A comparison between jazz and EDM is then build in order to make clear why jazz is an appropriate field of application for Benjamin’s intuitions.
Keywords: African Research